Analysis of drift characteristic in conductivity and temperature sensors used in Moored buoy system. (1st January 2019) - Venkatesan, Ramasamy; Ramesh, Krishnamoorthy; Arul Muthiah, Manickavasagam; Thirumurugan, Karuppiah; Atmanand, Malayath Aravindakshan
Abstract: Conductivity and Temperature (CT) sensors are attached in the Ocean Moored buoy network in Northern Indian Ocean (OMNI) at different depths upto 500 m below the sea surface. Drift in these sensors were analyzed based on the result of calibration. For detailed investigation, the sensor's drift is categorized based on the position of sensors in the mooring as surface layer (above 50 m), thermocline layer (50–200 m) and deep layer (200–500 m) and analysis was carried out at both Arabian Sea (AS) and Bay of Bengal BoB. The drift analysis revealed that over the time of deployment the drift in temperature sensor was very minimal and well within the accuracy limit. However, the drift in the conductivity sensors was more significant. Drift in the conductivity sensor decreases as the deployment depth of the sensor increases and also drift in the sensors which were deployed in AS is high as compared to the sensors deployed in BoB. Biofouling of the sensor is measured spatially in AS and BoB and it indicates that biofouling and Abrasive scouring of cells are due to the flow of high concentrations of plankton in the euphotic zone(top layer), which may cause the drift in the conductivity sensor. Highlights: Temperature sensor is very stable and drift is very minimum, irrespective of depth and period. Drift in the conductivity sensor is more significant, depends on depth. More drift in conductivity at surface layers and very less drift in the deep layers. Data correction based on post-cruise calibration shows an improvement in conductivity measurement. Bio-fouling affects the conductivity sensor in the surface and thermocline layer.